2021
DOI: 10.1093/jscr/rjab042
|View full text |Cite
|
Sign up to set email alerts
|

Splenic abscess after laparoscopic sleeve gastrectomy. A rare complication—case report and literature review

Abstract: Laparoscopic sleeve gastrectomy is currently a stand-alone bariatric procedure with a low complication profile. A rare complication of leak following sleeve gastrectomy was reported in this study. Its rareness and nonspecific clinical presentation could make the diagnosis difficult and could be easily confused with leak and subdiaphragmatic abscess. A 22-year-old Saudi female with body mass index 41 underwent laparoscopic sleeve gastrectomy in 2017, presented 18 months later to emergency department complaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…12 Again, Batayyah et al reported fistula and subdiaphragmatic abscess at the postoperative 18th month. 13…”
Section: Discussionmentioning
confidence: 99%
“…12 Again, Batayyah et al reported fistula and subdiaphragmatic abscess at the postoperative 18th month. 13…”
Section: Discussionmentioning
confidence: 99%